Indirect Spectrophotometric Determination of Paracetamol Via Decolorization of Eriochrom Black-T With N-Bromosuccinimide - Theiaa Al-Sabha; Zahraa Al-Gubouri (College of Education for Pure Sciences, 2020)
A simple, precise and sensitive indirect spectrophotometric method is described for the assay of Paracetamol in its pure form and pharmaceutical formulations in the aqueous medium. The method is based on the oxidation of the Paracetamol with an excess of N-Bromosuccinimide (NBS) in alkaline medium and the residual oxidizing agent bleaches the purple-colored Eriochrom black-T (EBT) to colorless species which is measured at 516 nm at room temperature. Calibration graph is linear over 0.5-9 µg mL-1 and molar absorptivity is 3.7×104 L.mol-1.cm-1. The detection and quantification limits were 0.068 and 0.229 µgmL-1 respectively. The accuracy (Average recovery %) is 98.57, and Precision (RSD) is ≤ 1.5. No interference effect has been observed from the excipients that exist in drug formulations. The method has been applied successfully in the determination of the Paracetamol in its commercial formulations (injection, syrup, and tablet), and compared favorably with other spectrophotometric methods used different reagents. The reaction mechanism for the oxidation of Paracetamol and EBT was postulated.